SWIFT beginnings – exploring the effectiveness and transformative character of a Summer Writing Institute For Teachers (SWIFT). Issue 2 (4th March 2019) - Farrell, Alison; ,
Abstract: The purpose of this article is to describe, examine, and make a case for the value of a Continuing Professional Development week-long summer institute offered to teachers from across the education continuum – from early childhood, through primary, secondary, further and higher education. At the institute participants could meet, learn and share good practice about their own writing and the teaching of writing. The institute was inspired by the United States National Writing Project model and was designed by staff of the Maynooth University Writing Centre, in partnership with the Bay Area Writing Project, University of California Berkeley, and in consultation with a range of Irish teaching and learning networks. This paper presents the background to and rationale for the institute, considers its effectiveness in terms of the model, the 'personality' and the impact of the summer institute, and suggests how the summer institute is transformative for participants.